2020
DOI: 10.3390/antiox9090851
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic vs. Natural Hydroxytyrosol for Clean Label Lamb Burgers

Abstract: Clean labelling refers to consumers’ desire for manufacturers to be more transparent in the way their products are made and sourced. Natural antioxidants (spices, herbs, fruits, or vegetables) have been proven to offer the same functionality as their synthetic counterparts, with the advantage of being label friendly and process compatible, maintaining meat quality and reducing food waste. Lamb meat has the challenges to have an intense flavour and fat composition to test the effectiveness of some of these natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
(75 reference statements)
2
9
0
Order By: Relevance
“…A higher antioxidant activity was found in the PE in comparison with the CM containing ascorbic acid (554.42 ± 3.38 and 1149.02 ± 13.69 µg TE/100 g in CM and PE, respectively). The high antioxidant activity recorded in the PE is in agreement with a previous studies that reported the powerful antioxidant activity of olive phenolic compounds [ 22 , 41 , 42 , 43 , 44 ]. The results for the lipid oxidation and antioxidant activity of minced beef meat indicated by TBARs and ORAC FL values are reported in Table 2 .…”
Section: Resultssupporting
confidence: 92%
“…A higher antioxidant activity was found in the PE in comparison with the CM containing ascorbic acid (554.42 ± 3.38 and 1149.02 ± 13.69 µg TE/100 g in CM and PE, respectively). The high antioxidant activity recorded in the PE is in agreement with a previous studies that reported the powerful antioxidant activity of olive phenolic compounds [ 22 , 41 , 42 , 43 , 44 ]. The results for the lipid oxidation and antioxidant activity of minced beef meat indicated by TBARs and ORAC FL values are reported in Table 2 .…”
Section: Resultssupporting
confidence: 92%
“…Obtained results can be supported by the rest of the assessed characteristics where the antioxidant and antimicrobial capacities of HT were demonstrated ( Figure 1 , Table 5 and Table 6 ). Additionally, the antioxidant activity of HT has been repeatedly demonstrated by several authors, as in vitro [ 36 , 37 , 38 ], as in vivo [ 39 , 40 , 41 , 42 , 43 , 44 ] or as a preserver in a food matrix [ 17 , 30 , 31 , 32 , 35 , 45 , 46 , 47 ]. For that, incorporation of this kind of products in a balanced Mediterranean Diet could report significant health benefits of consumers in comparison with usual manufactured meat products rich in synthetic additives.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important natural antioxidants is 3,4-dihydroxyphenylethanol or hydroxytyrosol (HXT), showing interesting antioxidant characteristics and having beneficial effects on health [ 62 ]. Martinez-Zamora et al [ 63 ] tested both natural (HXTo) and synthetic (HXTs) antioxidants on lamb meat burgers. Natural HXTo consisted of organic hydroxytyrosol (HXTo, sample 7% purity from olive tree leaves, 200 ppm) showed higher preservative activity in maintaining the nutritional value than the control synthetic HTX (HXTs, 99% purity, 200 ppm) made with sulphites.…”
Section: Clean-label Ingredients In Meat Productsmentioning
confidence: 99%